How to get research published in journals - Day, Abby (Gower, 2008)
Now in its second edition, this internationally best-selling book has been revised and updated. It focuses on helping people overcome some of the most common obstacles to successful publication. Lack of time? An unconscious fear of rejection? Conflicting priorities? In this, the first book to address the subject, Abby Day explains how to overcome these obstacles and create publishable papers for journals most likely to publish them. She shows how to identify a suitable journal and how to plan, prepare and compile a paper that will satisfy its requirements. She pays particular attention to the creative aspects of the process. As an experienced journal editor and publisher, Dr Day is well placed to reveal the inside workings of the reviewing procedure - and the more fully you understand this, the greater the chance that what you submit will be accepted and published. For academic and research staff, in whatever discipline, a careful study of Dr Day's book could be your first step on the road to publication. Contents: Preface. Part One Setting Your Objectives: Introduction; Why publish?; Why not publish?; A sense of purpose; So what?; Making sense of the literature. Part Two Knowing Your Audience: Who are the editors and reviewers?; Through the reader's eyes; Targeting journals. Part Three From Draft to Print: Seven days to a finished paper; Writing the draft; Points of style; Managing the process; Keeping it going. References; Index. Abby Day is the author and co-author of several books about publishing and funding and her 'How to Get Published' workshops are popular events in colleges and universities worldwide. With an MA and PhD in the sociology of religion, she also pursues her own research and publishing in that discipline. She is a Trustee of the British Sociological Association with responsibility for its publishing portfolio.